LEAVES UNDER LABOR LEGISLATION OF UKRAINE - Garashchenko, Liudmyla P. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
Purpose: the purpose of the present scientific work is to study the legislation of Ukraine on holidays and the use of separate articles of the Law of Ukraine "On leaves", which contain blanket norms. The system of sectoral legislation is considered, and the frames of its use are defined. Methods: optimization of legal enforcement of labor law norms, which regulates the procedure for granting leaves. Results: levels of legal regulation of leaves are determined and separate sub-legal acts are analyzed, which is important for law enforcement. Discussion: international normative acts, national legislation on the provision of certain types of leaves.